N-Terminal Type III Secretion Signal of Enteropathogenic Escherichia coli Translocator Proteins - Munera, Diana (American Society for Microbiology (ASM), 2010)
We report that the N terminus of the type III secretion system translocator proteins EspB, EspD, and EspA mediate protein secretion and translocation from wild-type enteropathogenic Escherichia coli and hypersecretion from sepL and sepD mutants. EspA containing the translocation signal of Map and Tir containing the secretion signal of EspA are biologically active.